Novecento: tempo presente o passato remoto? (Prassi Ecdotiche della Modernità Letteraria, 2017)
Il fascicolo monografico "Editori e filologi", che ha visto la luce nel 2014, contiene un mio intervento che fotografa la situazione del mondo editoriale all’altezza del 2013. Vorrei ripartire da lì, dall’ottimistica fiducia con cui lo concludevo, per le mie riflessioni odierne. 20th Century: present or past?The publishing industry has recently been involved into the digital revolution: digital editions are now the third element in publisher’s supply, in addition to the so-called ‘classics’ and the ‘front list’. It has caused many problems to publishers, especially in relation to 20th Century authors' works, which are in catalogues from long time but are not considered ‘classics’ yet.
Keywords: Editoria; tascabili; opere complete; scuola; classici; catalogo; canone